THU0023 DETAILED PROFILE OF CO-OCCURRENCE OF RELAPSING POLYCHONDRITIS AND AUTOIMMUNE THYROID DISEASE. (2nd June 2020) - Nakajima, T.; Yoshifuji, H.; Yamano, Y.; Handa, H.; Ohmura, K.; Mimori, T.; Terao, C.
Abstract : Background: Relapsing polychondritis (RP) is a rare inflammatory disease, which is characterized by recurrent inflammation and destruction of cartilage tissues. RP also has the profile of autoimmune disease and is often complicated with other autoimmune disease. Autoimmune thyroid disease (AITD) is one of common autoimmune diseases, which consists of Graves' disease (GD) and Hashimoto's thyroiditis (HT). While RP is reported to be complicated with AITD 1), there has been no study on detailed profile of co-occurrence of RP and AITD. Objectives: We aimed to reveal whether there is common (statistically significant) co-occurrence of RP and AITD. We also analyzed clinical and genetic profiles characterizing the co-occurrence. Methods: We recruited 117 patients with RP and checked their medical records in order to obtain the information about compilation of AITD and clinical features. In addition, we genotyped Human Leucocyte Antigen (HLA) A, B Cw, DRB1, DQB1 and DPB1 alleles for 88 of the 117 patients. Co-occurrence ratio was compared with prevalence of AITD in the Japanese population. Associations of co-occurrence of AITD with clinical manifestations or HLA alleles were analyzed among the patients. Results: Among the 117 patients with RP, 5 (4.3%) and 6 (5.1%) patients had GD and HT, respectively. Patients with RP were more likely to be complicated with GD (p=1.04×10 -3, OR: 7.15, 95%CI 2.68 18.14) but not with HT (p=0.50, 95%CI 0.59 1.27), compared with prevalence in general Japanese population (0.62% and 5.9%, respectively 2) ). RP patients with GD showed a trend to have nasal involvement (100% vs 45.5%, p=0.023, OR: 2.58, 95%CI 1.09 ∞). We did not observe any differences in clinical manifestation in patients with RP and HT. HLA- DPB1*02:02 demonstrated a trend toward GD complication (20% vs 2.3%, p=0.035, OR: 10.41, 95%CI 1.23 65.38). There were no association of HLA in the complication of HT among patients with RP. Conclusion: Patients with RP have high co-occurrence ratio of GD. Patients with the two diseases may be characterized by nasal involvement and HLA-DPB1*02:02. References: [1]Kung AW et al. Graves' ophthalmopathy and relapsing polychondritis. Clin Exp Rheumatol. 1995 Jul-Aug;13(4):501-3. [2]Nagataki S et al. Thyroid diseases among atomic bomb survivors in Nagasaki. JAMA. 1994 Aug 3;272(5):364-70. Disclosure of Interests: Toshiki Nakajima Speakers bureau: Bristol-Myers Squibb and Novartis, Hajime Yoshifuji Grant/research support from: Astellas Pharma. (Outside the field of the present study.), Speakers bureau: Chugai Pharmaceutical. (Outside the field of the present study.), Yoshihisa Yamano: None declared, Hiroshi Handa: None declared, Koichiro Ohmura Grant/research support from: Astellas Pharma, AYUMI Pharmaceutical, Chugai Pharmaceutical, Daiichi Sankyo, Eisai, Japan Blood Products Organization, Mitsubishi Tanabe Pharma, Nippon Kayaku, Nippon Shinyaku, Sanofi, and Takeda Pharmaceutical., Speakers bureau: AbbVie, Actelion Pharmaceuticals Japan, Asahi Kasei Pharma, AYUMI Pharmaceutical, Bristol-Myers Squibb, Chugai Pharmaceutical, Eisai, Eli Lilly and Company, GlaxoSmithKline, Janssen Pharmaceutical, Mitsubishi Tanabe Pharma, Novartis Pharma, and Sanofi., Tsuneyo Mimori: None declared, Chikashi Terao Grant/research support from: Actelion, Speakers bureau: Asteras, Asahi Kasei Pharma, Ono and Tanabe-Mitsubishi